The Key Problems of Intelligent Quality Control of Green Building are Analyzed Based on Computer Information Data. (June 2020) - Li, Shilan
Abstract: The development of computers has revolutionized the way we work.At the same time with the development of China's economy, China's construction industry has entered a period of rapid development.In terms of the economic contribution rate of various industries, in China's economy, the development of the construction industry accounts for a large part of the output value, but it has brought huge economic benefits, but also caused a series of environmental problems and construction safety and quality problems, which have seriously affected people's quality of life and the safety of life and property.This paper USES the computer information data technology to carry on the strict evaluation and control to each part of the building structure.So that it can effectively avoid security and other issues..